Overcoming barriers to oral contraception in Italy an expert opinion to empower women - Rossella E. Nappi; Manuela Farris; Achille Gallina Toschi; Raffaella Michieli; Francesca Moccia; Nicoletta Orthmann; Emilio Arisi (Taylor & Francis Group, 2023)
Oral contraceptives are among the most commonly used contraceptive methods. However, Italian women underused reliable hormonal contraceptives as compared with other European women. There is a need to streamline access to oral contraception, with expected benefits on emotional well-being of women and potential savings for health system in Italy. Indeed, women can only access to oral contraceptives through mandatory medical prescription. This is one of the most important barrier experienced by women. We hereby provide an expert opinion on the potential reclassification, extending pharmacy services to include responsible and appropriate use of POP, as an opportunity also in Italy to increase the use of safe and effective contraceptive methods.